2018
DOI: 10.1108/jima-10-2016-0076
|View full text |Cite
|
Sign up to set email alerts
|

Perception of the takaful operators’ performance towards customers’ intention in using medical takaful card among public sector

Abstract: Purpose This paper aims to examine the level and the relationship between the perception of the performance of takaful operators and the customers’ intention in using medical takaful card among public sectors in Kedah, Malaysia. Design/methodology/approach A quantitative research methodology was advocated to answer the objectives progressively. Data were collected from questionnaires and analyzed using SPSS v22. In total, 313 respondents were selected from three public sectors in Kedah, Malaysia. Findings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 33 publications
(36 reference statements)
0
6
0
Order By: Relevance
“…The TRA postulate that human behavior is thoroughly logical and it applies limited information that is at a person’s disposal (Tamjidyamcholo et al , 2013). Based on the assumption of behavior is founded on rationality, the TRA postulates a model conceptually applicable to entire human activities (Guo and Feng, 2012; Haji Wahab, 2018). Theory of reasoned action (TRA) is one of the three classic persuasion models of psychology.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…The TRA postulate that human behavior is thoroughly logical and it applies limited information that is at a person’s disposal (Tamjidyamcholo et al , 2013). Based on the assumption of behavior is founded on rationality, the TRA postulates a model conceptually applicable to entire human activities (Guo and Feng, 2012; Haji Wahab, 2018). Theory of reasoned action (TRA) is one of the three classic persuasion models of psychology.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Actually, this theory is used to predict how individuals behave based on their pre-existing attitudes and behavioral intentions. An individual’s decision to engage in a particular behavior is based on the outcomes of the expectations after performing the behavior (Haji Wahab, 2018).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Hasan (2022a) define perceived behavioral control as a function of control beliefs that refer to an individual's perception of the availability of opportunities or resources needed to perform a particular behavior. Besides, Wahab (2018) explain PBC as an individual's perception of how well he/she can manage factors that facilitate or constrain an individual's actions to perform a particular behavior in a specific situation. Earlier studies described that an individual's self-confidence, resources and opportunities positively influence FTPI Husin and Ab Rahman, 2013).…”
Section: Perceived Behavioral Control and Family Tak Aful Purchase In...mentioning
confidence: 99%
“…Out of 15 hypotheses, 12 were found to be significant. Wahab (2018) examined the level and relationship between the perception of the performance of Takaful operators and the customers intention to use medical Takaful cards among public sectors in Kedah, Malaysia. The review found that the level of customers perception of performance towards the customers intention to use the medical Takaful card was high.…”
Section: Literature Reviewmentioning
confidence: 99%